Scarcity cues, fear of missing out, and impulse buying behavior in fashion product: The role of Islamic religiosity - Dahmiri Dahmiri; Sylvia Kartika Wulan Bhayangkari; Raja Sharah Fatricia (LPMP Imperium, 2023)
The main objective of this study is to investigate the relationship between scarcity cues, FOMO, and impulse buying in Islamic fashion and cosmetic products in the online market. In addition, moderating roles of Islamic religiosity in these relationships were also verified. A sample of 234 female university students participated via an online questionnaire. Results of Moderating mediating analysis revealed that (a) scarcity cues are positively associated with FOMO and impulse buying; (b) FOMO has been confirmed positively associated with impulse buying; (c) all of these relationships are moderated by religiosity. The results underscore the importance of religiosity as a boundary condition, making it less likely to be involved in impulse buying than less religious individuals. Hence, it can be confirmed that Islamic religiosity emphasizes values such as self-control, discipline, and humility, which can help individuals avoid FOMO and impulsive buying behavior. Public interest statement This study provides new insights into studying impulse buying from the perspective of Islamic religiosity, scarcity cues, and FoMO simultaneously. This study emphasizes the critical role of Islamic religiosity as a boundary condition for FoMO and impulse buying among female consumers Article history Received: 1/21/2023 | Revised: 5/10/2023 | Accepted: 5/11/2023 | Online First: 5/11/2023